Conventional cooked and raw dog diets: Swiss owners’ risk perception and knowledge - Andrea Knörr; Angela Bearth; Xiao Zhou; Roger Stephan; Michael Siegrist (Preventive Veterinary Medicine, 2025)

Detection of OXA-23-producing Proteus mirabilis in Switzerland - Jacqueline Findlay; Patrice Nordmann; Roger Stephan; Laurent Poirel (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Hydrolysis probe assays for the detection of pathogenic Enterohemorrhagic Escherichia coli: Multi-Country validation study - Frank J. Velez; Joseph M. Bosilevac; Gloria Salazar; Harsimran Kaur Kapoor; Abhinav Mishra; Evelyn Madoroba; Kim Stanford; Patrick Fach; Sabine Delannoy; Roger Stephan; Prashant Singh (Food Research International, 2024)

Genetic diversity and antimicrobial susceptibility of Streptococcus suis from diseased Swiss pigs collected between 2019 – 2022 - Simone Scherrer; Michael Biggel; Marianne Schneeberger; Nicole Cernela; Fenja Rademacher; Sarah Schmitt; Roger Stephan (Veterinary Microbiology, 2024)

Antimicrobial resistance and phylogenetic relatedness of extended-spectrum ß-lactamase (ESBL)-producing Escherichia coli in peridomestic rats (Rattus norvegicus and Rattus tanezumi) linked to city areas and animal farms in Hong Kong - Theethawat Uea-Anuwong; Michael Biggel; Nicole Cernela; Wu Wai Hung; Kittitat Lugsomya; Lam Hoi Kiu; Yrjö Tapio Gröhn; Sara Boss; Roger Stephan; Magdalena Nüesch-Inderbinen; Ioannis Magouras (Environmental Research, 2024)

Top predator feeding ecology and microplastic (MP) contamination on the far eastern South American coast: Evidence of MP trophic biotransfer - Roger R.R.C.B. Melo; Mário Barletta; Francisco F.J.A. Cysneiros; Maria Inês B. Tavares; Karoline da Silva Santana; Stephan Carty; Simon A. Morley (Estuarine, Coastal and Shelf Science, 2024)

Dissemination of ESBL-producing E. coli ST131 through wastewater and environmental water in Switzerland - Michael Biggel; Sarah Hoehn; Andrea Frei; Kira Dassler; Christoph Jans; Roger Stephan (Environmental Pollution, 2023)

Cerebellar Effects on Abnormal Psychomotor Function Are Mediated by Processing Speed in Psychosis Spectrum - Alexandra B. Moussa-Tooks; Jinyuan Liu; Kristan Armstrong; Baxter Rogers; Neil D. Woodward; Stephan Heckers (The Cerebellum, 2023)

Intermittent instability is widespread in plankton communities - Tanya L. Rogers; Stephan B. Munch; Shin‐ichiro S. Matsuzaki; Celia C. Symons (Ecology Letters, 2023)
Chaotic dynamics appear to be prevalent in short‐lived organisms including plankton and may limit long‐term predictability. However, few studies have explored how dynamical stability varies through time, across space and at different taxonomic resolutions. Using plankton time series data from 17 lakes and 4 marine sites, we found seasonal patterns of local instability in many species, that short‐term predictability was related to local instability, and that local instability occurred most often in the spring, associated with periods of high growth. Taxonomic aggregates were more stable and more predictable than finer groupings. Across sites, higher latitude locations had higher Lyapunov exponents and greater seasonality in local instability, but only at coarser taxonomic resolution. Overall, these results suggest that prediction accuracy, sensitivity to change and management efficacy may be greater at certain times of year and that prediction will be more feasible for taxonomic aggregates.

Soil–plant interactions modulated water availability of Swiss forests during the 2015 and 2018 droughts - Katrin Meusburger; Volodymyr Trotsiuk; Paul Schmidt‐Walter; Andri Baltensweiler; Philipp Brun; Fabian Bernhard; Mana Gharun; Raphael Habel; Frank Hagedorn; Roger Köchli; Achilleas Psomas; Heike Puhlmann; et al. (Global Change Biology, 2022)
Central Europe has been experiencing unprecedented droughts during the last decades, stressing the decrease in tree water availability. However, the assessment of physiological drought stress is challenging, and feedback between soil and vegetation is often omitted because of scarce belowground data. Here we aimed to model Swiss forests' water availability during the 2015 and 2018 droughts by implementing the mechanistic soil‐vegetation‐atmosphere‐transport (SVAT) model LWF‐Brook90 taking advantage of regionalized depth‐resolved soil information. We calibrated the model against soil matric potential data measured from 2014 to 2018 at 44 sites along a Swiss climatic and edaphic drought gradient. Swiss forest soils' storage capacity of plant‐available water ranged from 53 mm to 341 mm, with a median of 137 ± 42 mm down to the mean potential rooting depth of 1.2 m. Topsoil was the primary water source. However, trees switched to deeper soil water sources during drought. This effect was less pronounced for coniferous trees with a shallower rooting system than for deciduous trees, which resulted in a higher reduction of actual transpiration (transpiration deficit) in coniferous trees. Across Switzerland, forest trees reduced the transpiration by 23% (compared to potential transpiration) in 2015 and 2018, maintaining annual actual transpiration comparable to other years. Together with lower evaporative fluxes, the Swiss forests did not amplify the blue water deficit. The 2018 drought, characterized by a higher and more persistent transpiration deficit than in 2015, triggered widespread early wilting across Swiss forests that was better predicted by the SVAT‐derived mean soil matric potential in the rooting zone than by climatic predictors. Such feedback‐driven quantification of ecosystem water fluxes in the soil–plant‐atmosphere continuum will be crucial to predicting physiological drought stress under future climate extremes.

Applying empirical dynamic modeling to distinguish abiotic and biotic drivers of population fluctuations in sympatric fishes - Ben A. Wasserman; Tanya L. Rogers; Stephan B. Munch; Eric P. Palkovacs (Limnology and Oceanography, 2022)
Fluctuations in the population abundances of interacting species are widespread. Such fluctuations could be a response to abiotic factors, biotic interactions, or a combination of the two. Correctly identifying the drivers is critical for effective population management. However, such effects are not always static in nature. Nonlinear relationships between abiotic factors and biotic interactions make it difficult to parse true effects. We used a type of nonlinear forecasting, empirical dynamic modeling, to investigate the context‐dependent species interaction between a common fish (three‐spine stickleback) and an endangered one (northern tidewater goby) in a fluctuating environment: a central California bar‐built estuary. We found little evidence for competition, instead both species largely responded independently to abiotic conditions. Stickleback were negatively affected by sandbar breaching. The strongest predictor of tidewater goby abundance was stickleback abundance; however, this effect was not a uniform negative effect of stickleback on goby as would be hypothesized under interspecific competition. The effect of stickleback on gobies was positive, though it was temporally restricted. Tidewater goby abundance in the summer was strongly positively correlated to stickleback abundance in the spring, which represents an offset in the reproductive and recruitment peaks in the two species that may help minimize competition and promote coexistence. Our study demonstrates how empirical dynamic modeling can be applied to understand drivers of population abundance in putative competitors and inform management for endangered species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Lineage‐specific evolution and gene flow in Listeria monocytogenes are independent of bacteriophages - Roxana Zamudio; Richard D. Haigh; Joseph D. Ralph; Megan De Ste Croix; Taurai Tasara; Katrin Zurfluh; Min Jung Kwun; Andrew D. Millard; Stephen D. Bentley; Nicholas J. Croucher; Roger Stephan; Marco R. Oggioni (Environmental Microbiology, 2020)
Summary Listeria monocytogenes is a foodborne pathogen causing systemic infection with high mortality. To allow efficient tracking of outbreaks a clear definition of the genomic signature of a cluster of related isolates is required, but lineage‐specific characteristics call for a more detailed understanding of evolution. In our work, we used core genome MLST (cgMLST) to identify new outbreaks combined to core genome SNP analysis to characterize the population structure and gene flow between lineages. Whilst analysing differences between the four lineages of L . monocytogenes we have detected differences in the recombination rate, and interestingly also divergence in the SNP differences between sub‐lineages. In addition, the exchange of core genome variation between the lineages exhibited a distinct pattern, with lineage III being the best donor for horizontal gene transfer. Whilst attempting to link bacteriophage‐mediated transduction to observed gene transfer, we found an inverse correlation between phage presence in a lineage and the extent of recombination. Irrespective of the profound differences in recombination rates observed between sub‐lineages and lineages, we found that the previously proposed cut‐off of 10 allelic differences in cgMLST can be still considered valid for the definition of a foodborne outbreak cluster of L . monocytogenes .

Trophic control changes with season and nutrient loading in lakes - Tanya L. Rogers; Stephan B. Munch; Simon D. Stewart; Eric P. Palkovacs; Alfredo Giron‐Nava; Shin‐ichiro S. Matsuzaki; Celia C. Symons (Ecology Letters, 2020)
Experiments have revealed much about top‐down and bottom‐up control in ecosystems, but manipulative experiments are limited in spatial and temporal scale. To obtain a more nuanced understanding of trophic control over large scales, we explored long‐term time‐series data from 13 globally distributed lakes and used empirical dynamic modelling to quantify interaction strengths between zooplankton and phytoplankton over time within and across lakes. Across all lakes, top‐down effects were associated with nutrients, switching from negative in mesotrophic lakes to positive in oligotrophic lakes. This result suggests that zooplankton nutrient recycling exceeds grazing pressure in nutrient‐limited systems. Within individual lakes, results were consistent with a ‘seasonal reset’ hypothesis in which top‐down and bottom‐up interactions varied seasonally and were both strongest at the beginning of the growing season. Thus, trophic control is not static, but varies with abiotic conditions – dynamics that only become evident when observing changes over large spatial and temporal scales.

Whole-Genome Sequencing of Aspergillus terreus Species Complex - Mathangi Palanivel; Micheál Mac Aogáin; Rikky W. Purbojati; Akira Uchida; Ngu War Aung; Serene B. Y. Lim; Alexander Putra; Daniela I. Drautz-Moses; Shila Seaton; Thomas R. Rogers; Stephan C. Schuster; Sanjay H. Chotirmall (Mycopathologia, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Population structure and virulence gene profiles of Streptococcus agalactiae collected from different hosts worldwide - Marina Morach; Roger Stephan; Sarah Schmitt; Christa Ewers; Michael Zschöck; Julian Reyes-Velez; Urs Gilli; María del Pilar Crespo-Ortiz; Margaret Crumlish; Revathi Gunturu; Claudia A. Daubenberger; Margaret Ip; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Continental mapping of forest ecosystem functions reveals a high but unrealised potential for forest multifunctionality - Fons van der Plas; Sophia Ratcliffe; Paloma Ruiz‐Benito; Michael Scherer‐Lorenzen; Kris Verheyen; Christian Wirth; Miguel A. Zavala; Evy Ampoorter; Lander Baeten; Luc Barbaro; Cristina C. Bastias; Jürgen Bauhus; et al. (Ecology Letters, 2018)
Humans require multiple services from ecosystems, but it is largely unknown whether trade‐offs between ecosystem functions prevent the realisation of high ecosystem multifunctionality across spatial scales. Here, we combined a comprehensive dataset (28 ecosystem functions measured on 209 forest plots) with a forest inventory dataset (105,316 plots) to extrapolate and map relationships between various ecosystem multifunctionality measures across Europe. These multifunctionality measures reflected different management objectives, related to timber production, climate regulation and biodiversity conservation/recreation. We found that trade‐offs among them were rare across Europe, at both local and continental scales. This suggests a high potential for ‘win‐win’ forest management strategies, where overall multifunctionality is maximised. However, across sites, multifunctionality was on average 45.8‐49.8% below maximum levels and not necessarily highest in protected areas. Therefore, using one of the most comprehensive assessments so far, our study suggests a high but largely unrealised potential for management to promote multifunctional forests.

Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Sophia Ratcliffe; Christian Wirth; Tommaso Jucker; Fons van der Plas; Michael Scherer‐Lorenzen; Kris Verheyen; Eric Allan; Raquel Benavides; Helge Bruelheide; Bettina Ohse; Alain Paquette; Evy Ampoorter; et al. (Ecology Letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.

Occurrence of Salmonella, L. monocytogenes, Shigatoxin-producing E. coli and ESBL-producing Enterobacteriaceae in sprout samples collected from the Swiss market - Heike Margot; Rebecca Ebner; Sophie Peterhans; Roger Stephan (Journal of Consumer Protection and Food Safety, 2016)

Characteristics of Listeria monocytogenes isolated from tonsils of slaughtered fattening pigs in Switzerland - Eleonora Sarno; Lisa Fierz; Claudio Zweifel; Taurai Tasara; Roger Stephan (Journal of Consumer Protection and Food Safety, 2016)

Epidemiology of Extended-Spectrum β-Lactamase-Producing Escherichia coli in the Human-Livestock Environment - Magdalena Nüesch-Inderbinen; Roger Stephan (Current Clinical Microbiology Reports, 2016)

Suppression of PPARβ, and DHA treatment, inhibit NaV1.5 and NHE-1 pro-invasive activities - Ramez Wannous; Emeline Bon; Ludovic Gillet; Julie Chamouton; Günther Weber; Lucie Brisson; Jacques Goré; Philippe Bougnoux; Pierre Besson; Sébastien Roger; Stephan Chevalier (Pflügers Archiv - European Journal of Physiology, 2015)

Controls of dissolved organic matter quality: evidence from a large‐scale boreal lake survey - Dolly N. Kothawala; Colin A. Stedmon; Roger A. Müller; Gesa A. Weyhenmeyer; Stephan J. Köhler; Lars J. Tranvik (Global Change Biology, 2014)
Inland waters transport large amounts of dissolved organic matter ( DOM ) from terrestrial environments to the oceans, but DOM also reacts en route, with substantial water column losses by mineralization and sedimentation. For DOM transformations along the aquatic continuum, lakes play an important role as they retain waters in the landscape allowing for more time to alter DOM . We know DOM losses are significant at the global scale, yet little is known about how the reactivity of DOM varies across landscapes and climates. DOM reactivity is inherently linked to its chemical composition. We used fluorescence spectroscopy to explore DOM quality from 560 lakes distributed across Sweden and encompassed a wide climatic gradient typical of the boreal ecozone. Six fluorescence components were identified using parallel factor analysis ( PARAFAC ). The intensity and relative abundance of these components were analyzed in relation to lake chemistry, catchment, and climate characteristics. Land cover, particularly the percentage of water in the catchment, was a primary factor explaining variability in PARAFAC components. Likewise, lake water retention time influenced DOM quality. These results suggest that processes occurring in upstream water bodies, in addition to the lake itself, have a dominant influence on DOM quality. PARAFAC components with longer emission wavelengths, or red‐shifted components, were most reactive. In contrast, protein‐like components were most persistent within lakes. Generalized characteristics of PARAFAC components based on emission wavelength could ease future interpretation of fluorescence spectra. An important secondary influence on DOM quality was mean annual temperature, which ranged between −6.2 and +7.5 °C. These results suggest that DOM reactivity depends more heavily on the duration of time taken to pass through the landscape, rather than temperature. Projected increases in runoff in the boreal region may force lake DOM toward a higher overall amount and proportion of humic‐like substances.

Grazing changes topography-controlled topsoil properties and their interaction on different spatial scales in a semi-arid grassland of Inner Mongolia, P.R. China - Angelika Kölbl; Markus Steffens; Martin Wiesmeier; Carsten Hoffmann; Roger Funk; Julia Krümmelbein; Agnieszka Reszkowska; Ying Zhao; Stephan Peth; Rainer Horn; Marcus Giese; Ingrid Kögel-Knabner (Plant and Soil, 2011)

Up–Down Asymmetry of Cerebellar Activation During Vertical Pursuit Eye Movements - Stefan Glasauer; Thomas Stephan; Roger Kalla; Sarah Marti; Dominik Straumann (The Cerebellum, 2009)

Different response to eccentric and concentric training in older men and women - Matthias Mueller; Fabio Andreas Breil; Michael Vogt; Roger Steiner; Kurt Lippuner; Albrecht Popp; Stephan Klossner; Hans Hoppeler; Christoph Däpp (European Journal of Applied Physiology, 2009)

Common input to different regions of biceps brachii long head - Benjamin K. Barry; Michael A. Pascoe; Stephan Riek; Richard G. Carson; Roger M. Enoka (Experimental Brain Research, 2009)

Mind the bend: cerebral activations associated with mental imagery of walking along a curved path - Judith Wagner; Thomas Stephan; Roger Kalla; Hartmut Brückmann; Michael Strupp; Thomas Brandt; Klaus Jahn (Experimental Brain Research, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Biologically relevant sex differences for fitness-related parameters in active octogenarians - Fabian Lötscher; Tobias Löffel; Roger Steiner; Michael Vogt; Stephan Klossner; Albrecht Popp; Kurt Lippuner; Hans Hoppeler; Christoph Däpp (European Journal of Applied Physiology, 2007)